TIMP-1 and responsiveness to gemcitabine in advanced breast cancer; results from a randomized phase III trial from the Danish breast cancer cooperative group - Jørgensen, Charlotte Levin Tykjær (BioMed Central, 2014)
BACKGROUND: Tissue inhibitor of metalloproteinases-1 (TIMP-1) has anti-apoptotic functions, which may protect TIMP-1 positive cancer cells from the effects of chemotherapy such as docetaxel and gemcitabine. The purpose of the present study was to evaluate TIMP-1 immunoreactivity as a prognostic and predictive marker in advanced breast cancer patients receiving docetaxel (D) or gemcitabine plus docetaxel (GD). METHODS: Patients with locally advanced or metastatic breast cancer who were assigned to D or GD by participation in a randomized phase III trial were included in the study. Assessment of TIMP-1 status was performed retrospectively on primary tumor whole-tissue sections by immunohistochemistry and tumor samples were considered positive if epithelial breast cancer cells were stained by the anti-TIMP-1 monoclonal antibody VT7. Time to progression (TTP) was the primary endpoint. Overall survival (OS) and response rate (RR) were secondary endpoints. Associations between TIMP-1 status and outcome after chemotherapy were analyzed by Kaplan-Meier estimates and Cox proportional hazards regression models. RESULTS: TIMP-1 status was available from 264 of 337 patients and 210 (80%) of the tumors were classified as cancer cell TIMP-1 positive. No significant difference for TTP between TIMP-1 positive versus TIMP-1 negative patients was observed in multivariate analysis, and RR did not differ according to TIMP-1 status. However, patients with TIMP-1 positive tumors had a significant reduction in OS events (hazard ratio = 0.71, 95% confidence interval (CI) = 0.52-0.98, P = 0.03). Additionally, a borderline significant interaction for OS was observed between TIMP-1 status and benefit from GD compared to D (P(interaction) = 0.06) such that median OS increased by nine months for TIMP-1 negative patients receiving GD. CONCLUSIONS: TIMP-1 status was an independent prognostic factor for OS but not TTP in patients with advanced breast cancer receiving either D or GD. There was no statistically significant interaction between TIMP-1 status and treatment, but a trend towards an incremental OS from the addition of gemcitabine to docetaxel in patients with TIMP-1 negative tumors suggests further investigation.